Compaction Density Determination of the Road Asphalt Layers - Cihlarova, Denisa; Mondschein, Petr; Capayova, Silvia (Communications - Scientific letters of the University of Zilina, 2018)
This paper analyses the destructive and non-destructive methods for checking the degree of compaction of asphalt layers and their multi-criteria evaluation. The data obtained during laying of ACO 11+50 mm thickness was selected for the analysis. The bulk density was determined by using probes Troxler 3440, Troxler 2701 and from the drill cores in these given locations. According to the analysis accuracy, the probe Troxler 2701 used to determine the final degree of compaction of the construction asphalt layer and for the routine control of compaction is not suitable, even though when applying AHP (Analytic Hierarch Process) it was assessed as the second most suitable one.